Dystopia and the Modern Subject - Perez, Dolores Christina (My University, 2000)
This dissertation explores the connections between dystopia and modern theorizations of human subjectivity in Aldous Huxley's Brave New World and George Orwell's Nineteen Eighty-Four. These two pioneering dystopias confront their reader's understanding of being human, as well as considering notions of responsibility, freedom, self and subjectivity by challenging modern assumptions of the nature of human reality. My introduction considers dystopia, and both authors' philosophical concerns as they emerge in the citizens of their dystopian worlds. These citizens function as analogies to the modern self that has gone astray and fallen into a state of nihilism. My second chapter focuses on the ethical construction of the citizens of Huxley's Brave New World and explores his critique of the ethics of scientism which shapes and influences their lives. My third chapter similarly considers the ideological complexities of the citizens in Orwell's even harsher dystopia Nineteen Eighty-Four, where ideology threatens the prospect of meaningful being in the world. By examining the way Huxley and Orwell meditate on the malaise of the modern self through their dystopian citizens, and identifying, with the help of modern theories on the self, their philosophical position on humanity's present condition, this study considers the great value of the modern dystopia. I highlight the importance of the dystopian search for a deeper understanding of the truth of reality, and meditate on the nature of being human, as dystopia describes what humanity is by describing what it is not.
Keywords: English; English Language and Literature; English Language and Literature